DETERMINATION OF JUSTICE COLLABORATOR IN THE INDONESIAN CRIMINAL JUSTICE SYSTEM: ANALYSIS OF SNG DISTRICT COURT DECISION NUMBER 79/PID.B/2024 - Tawaqal, Muhammad Fauzan; Ramada, Diandra Preludio (EKSEKUSI, 2025)
This study analyzes the procedures for designating a justice collaborator within Indonesia’s criminal justice system, using the case of *Sang District Court Decision No. 79/Pid.B/2024* involving convict Muhammad Ramdanu as a case study. The justice collaborator mechanism serves as a critical instrument to overcome evidentiary challenges in prosecuting organized crimes, particularly when conventional evidence is insufficient. The research employs a normative-juridical approach with qualitative analysis of legal frameworks, including Supreme Court Circular Letter (SEMA) No. 4 of 2011, Law No. 31 of 2014, LPSK Regulation No. 2 of 2020 (Witness and Victim Protection Agency), and Satjipto Rahardjo’s progressive legal theory. The findings reveal that the designation process for a justice collaborator involves a written application, verification of formal and material requirements, review by the LPSK, and recommendations for protective measures. Muhammad Ramdanu was deemed eligible as a justice collaborator due to his role as a non-principal perpetrator in the murders of Tuti Suhartini and Amalia Mustika Ratu, his significant informational contributions to uncovering the mastermind (Yosep Hidayah), and credible threats to his safety. This designation aligns with progressive legal principles that emphasize legal flexibility to achieve substantive justice. Implications include reduced sentencing and physical protection for justice collaborators. However, the study identifies regulatory gaps requiring clarification of "non-principal perpetrator" criteria and improved mitigation of retaliation risks. The findings recommend holistic policy integration between legal instruments and enforcement practices to ensure the efficacy of the justice collaborator mechanism without compromising fair trial principles and human rights.